Analysis and Construction of Geometric Patterns of Stone Ornaments of Susuz Inn - Zülal Nurdan Korur (Art-Sanat)
This research proposes a method to explain how the geometric patterns on the portal of Burdur Susuz Inn were created by the builders of the time. By combining basic geometry knowledge, common construction tools of the period, the compass-ruler method, and tessellation principles, the study aims to understand the increasing complexity of these patterns. Starting from the 9th century, Islamic geometric patterns gained momentum due to mathematical advancements. The research focuses specifically on Susuz Inn because of its unique geometric patterns and different typologies. It also explores the historical context and characteristics of the period when Susuz Inn was constructed to capture the spirit of the era. The study meticulously examines the fifth geometric patterns and the muqarnas on the portal of Susuz Inn, providing a detailed, step-by-step method from initial sketches to precise drawings. This transition from rough sketches to detailed drawings is thoroughly analyzed to contribute to the understanding and appreciation of the discipline. By addressing these aspects, the research aims to provide a comprehensive understanding of the geometric patterns on the portal of Susuz Inn and their historical and mathematical significance.